INTELLECTUAL CULTURE AND ITS ROLE IN SOCIAL DEVELOPMENT (TAMADDUN NURI JURNALI, 2025)
This article examines the essence of intellectuality and its role in the spiritual and moral development of society. It is emphasized that the maturity of a person is determined by the level of intelligence, which is formed through his theoretical knowledge and practical experience acquired in the process of self-development. Particular attention is paid to the relationship between intelligence and professional activity, worldview and moral and ethical values.